In silico analysis of Abrus precatorius L. as a potential agonist of PPARγ : A novel approach to the treatment of diabetes - Grace R. Michael* (International Journal of Molecular Biotechnological Research, 2025)
Diabetes mellitus is a chronic disorder that is characterized by a lack of insulin secretion by the pancreas or a defect in insulin action, or both. If diabetes is not controlled, over time it can cause damage to blood vessels and nerves, leading to life-threatening complications such as, kidney damage, heart disease and vision impairment. It can also weaken the immune system, making patients more prone to infection. Although treatments for diabetes has improved over the past few decades, mortality rates due to diabetes and its complications have been on the rise. Moreover, some hyperglycemic agents have been shown to induce irreversible side effects. Therefore, there is an urgent need to explore alternative therapeutic treatments to combat this disease. Peroxisome proliferator-activated receptor gamma (PPARγ) is an important protein that helps regulate glucose levels in the blood. This study explores the potential modulation of PPARγ by phytochemical compounds. In many countries including India, medicinal plants have been used as anti-diabetic agents. Abrus precatorius Linn is an important herb commonly known as rosary pea and abundantly found throughout India. A.precatorius can be used to treat a variety of diseases as various parts of the plants have different pharmacological activity, such as anti-diabetic, anti-oxidative, anti- inflammatory, anti-microbial and neuro-protective effects. The phytochemicals were extracted from the Indian Medicinal Plants, Phytochemistry and Therapeutics(IMPPAT). PyRx, an in-silico tool was then used to perform molecular docking simulations in order to find the lead compounds. The phytochemical compounds kaempferol, carvacrol, abrine, thymol methyl ether, and thymol which had the highest binding affinities with PPARγ were selected for further in silico analysis and pharmacological evalution was carried out on the basis of ADMET properties, which was performed in ADMETlab. The compound kaempferol showed the highest binding affinity with PPARγ. Its molecular interaction with PPARγ was captured on Biovia Discovery Studio Visualizer.
Keywords: Abrus precatorius L; BIOVIA; Bioinformatics; Diabetes mellitus; IMPPAT database; Peroxisome proliferator-activated receptor gamma (PPARγ); PyRx; kaempferol; molecular docking